Canning Process Lemuru Fish (Sardinella longiceps) in CV. Pasific Harvest, Banyuwangi, East java. - Arini Arini; Sri Subekti (Journal of Marine and Coastal Science, 2019)
Fish is a perishable food source, there the one processing need to be done with fast and right. Fish processing principle is basically aimed for protecting fish from decay and harm with extend to durable power. One of them by canning namely the form of processing and preservation modern fish to that are packaged in hermatik which then sterilized. Working method used is descriptive research with technique of data collection such as primary and secondary data with manner to active participation, observation and interviews. Practice Field Activity was held on January 14 to February 14, 2013 in CV. Pasific Harvest Banyuwangi, East Java. Fish canning process includes acceptance fish, tail and head fish cutting, fish filling, steaming, filling oil, closing cans, sterilization products, and incubation. Every stage the process of canning lemuru fish (Sardinella longiceps)  have an important role on the quality of the fish canning. The results of the activities of Field Work Practice was the company has implemented the process of canning lemuru fish (Sardinella longiceps) in accordance with GMP and SSOP. Stages of the canning process can be fish cutting, fish filling into cans, steaming, provision of additional medium, closing cans and sterilization. The supporting factors this process is the feasibility of materials, smoothness canning tools, awareness of workers will be the task and cleanliness.